Psychology in black and white : the project of a theory-driven science - Salvatore, Sergio, 1965- (Advances in cultural psychology., 2016)
This book is long awaited within the contemporarily creative field of cultural psychologies. It is a theoretical synthesis that is at the level of innovations that Sigmund Freud, James Mark Baldwin, William Stern, Kurt Lewin, Jean Piaget, Lev Vygotsky and Jan Smedslund have brought into psychology over the past century. Here we can observe a creative solution to integrating cultural psychology with the rich traditions of psychodynamic perspectives, without repeating the conceptual impasses in which many psychoanalytic perspectives have become caught.